Dekonstruksi Patriarki: Pemikiran Nawal El Saadawi dan Relevansinya dalam Budaya Matriarkat Minangkabau - Afriko, Nofik; Rusydi Am; Riki Saputra; Sri Wahyuni (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This article explores the thought of Nawal El Saadawi regarding women's rights through the lens of Islamic law and its relevance to the matriarchal culture of the Minangkabau society. Utilizing a descriptive qualitative approach and library research methods, the study analyzes Saadawi’s autobiographical and fictional works, which articulate a sharp critique of patriarchal systems that oppress women through state power, cultural norms, and gender-biased religious interpretations. The data analysis is conducted through an interpretive-hermeneutic method, aiming to uncover Saadawi’s transformative and progressive ideas within the framework of Islam. The research also incorporates data triangulation by referencing national and international scholarly journals from the past decade to strengthen the theoretical validity of the arguments presented. The findings reveal that while Saadawi's ideas are often perceived as controversial, they align with the Islamic principles of justice and gender equality, as reflected in the Qur'an. Furthermore, when contextualized within the Minangkabau matrilineal tradition, it becomes evident that Islamic feminism has long been integrated into local customs—placing women at the center of lineage and granting them significant roles in both domestic and public spheres, exemplified by the figure of Bundo Kanduang. This article concludes that Saadawi’s feminist perspective and the cultural values of the Minangkabau can serve as ideological and cultural foundations for developing a more gender-inclusive Islamic discourse and as an alternative model for the advancement of women's rights in contemporary Muslim societies.